Trauma From Occlusion: Does It Affect The Periodontium? A Review (The Quintessential, 2024)
Mastication is the major function of the dentition and since the periodontium constitutes the supporting mechanism which enables the teeth to fulfil this function, consideration of the interrelation between occlusal forces and the periodontium is basic in periodontology. The etiology of periodontal disease is multifactorial. One of the factors, thought to be responsible for the initiation of inflammatory periodontal disease, is occlusal trauma. Although a variety of occlusal conditions have reportedly been related to inflammatory periodontal disease (e.g. bruxism, malocclusion, abfraction etc.).